Assessment of fibre optic strain gauges for field use in India. (2015) - Scott, Richard H.; Banerji, Pradipta; Chikermane, Sanjay; Surre, Frederic; Sun, Tong; Grattan, Kenneth T.V.
The commissioning and evaluation of a fibre optic strain sensor system for the structural health monitoring of a pre-stressed concrete post-tensioned box girder railway bridge in operational use in Mumbai, India, is described. Preliminary laboratory trials to identify the most appropriate sensor system are detailed followed by a description of the load tests on the actual bridges which were undertaken in collaboration with Indian railways. Results from the load tests using the optical system are compared with similar results obtained using electrical resistance strain gauges. Conclusions are drawn concerning the integrity of the structure and for the future use of the sensor system for monitoring bridges of this type. Crack width measurements obtained during the load tests are also summarised.